2015
DOI: 10.1074/jbc.m115.671115
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Cellular Assembly Stoichiometry of Polycomb Complexes on Chromatin Revealed by Single-molecule Chromatin Immunoprecipitation Imaging

Abstract: Background: Polycomb proteins control transcription by regulating chromatin structure and dynamics. Results: By developing and applying a novel Sm-ChIPi technique, we identified that one PRC1 binds multiple nucleosomes within cells, although two PRC2s can bind a single nucleosome. Conclusion: PRC1 and PRC2 complexes employ distinct mechanisms to assemble on chromatin. Significance: The cellular assembly stoichiometry provides insight into repressive polycomb chromatin structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 77 publications
5
27
0
Order By: Relevance
“…To resolve this possibility, we integrated YFP-CBX2 and HT-CBX2 into the genome of Cbx2 Ϫ/Ϫ mES cells. Under the basal expression, the protein level of YFP-CBX2 was similar to that of the endogenous protein CBX2 (45). Without doxycycline induction, the distribution of YFP-CBX2 and HT-CBX2 in Cbx2 Ϫ/Ϫ mES cells was similar to that in WT mES cells (Fig.…”
Section: Cbx2 Forms Condensates In Cellsmentioning
confidence: 62%
“…To resolve this possibility, we integrated YFP-CBX2 and HT-CBX2 into the genome of Cbx2 Ϫ/Ϫ mES cells. Under the basal expression, the protein level of YFP-CBX2 was similar to that of the endogenous protein CBX2 (45). Without doxycycline induction, the distribution of YFP-CBX2 and HT-CBX2 in Cbx2 Ϫ/Ϫ mES cells was similar to that in WT mES cells (Fig.…”
Section: Cbx2 Forms Condensates In Cellsmentioning
confidence: 62%
“…During evolution, the number of genes encoding Cbx proteins has increased, which has resulted in structural and functional diversification ( Cheng et al, 2014 ; Klauke et al, 2013 ; Morey et al, 2012 ; Ren and Kerppola, 2011 ; Ren et al, 2008 ; Tatavosian et al, 2015 ; Vincenz and Kerppola, 2008 ; Whitcomb et al, 2007 ; Zhen et al, 2014 ). At the single-molecule level, we quantified the kinetic fractions of the Cbx proteins within living mES cells and revealed that ∼ 30% of Cbx2, Cbx7, and Cbx8 associate with chromatin at a given time period while ∼10–15% of Cbx4 and Cbx6 bind to chromatin.…”
Section: Discussionmentioning
confidence: 99%
“…These mES cells were maintained in mES medium (DMEM (D5796; Sigma-Aldrich, St Louis, MO) supplemented with 15% FBS (F0926; Sigma-Aldrich, St Louis, MO), 2 mM glutamine (25030–081; Life Technologies, Carlsbad, CA), 100 units/ml penicillin-streptomycin (15140–122; Life Technologies, Carlsbad, CA), 0.1 mM β-mercaptoethanol (21985–023; Life Technologies, Carlsbad, CA), 10 3 units/ml leukemia inhibitor factor (LIF) and 0.1 mM non-essential amino acids (1114050; Life Technologies, Carlsbad, CA)) at 37°C in 5% CO 2 . 4-hydroxytamoxifen (OHT; H7904; Sigma-Aldrich Inc, St Louis, MO) was administrated to deplete the Ring1b alleles of the Ring1a −/− /Ring1b fl/fl ; Rosa26::CreERT2 mES cells ( Tatavosian et al, 2015 ; Zhen et al, 2014 ). HEK293T cells were maintained as described previously ( Tatavosian et al, 2015 ; Zhen et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations